Metabolic Disorders And Periodontal Disease: A Scoping Review Of Recent Studies - Rafisa, Anggun; Febriane Balafif, Felisha; Najmi, Nuroh; Kuswandani, Faisal (Sean Institute, 2024)
The bidirectional relationship between periodontal disease and metabolic disorders is of particular concern, as these conditions may exacerbate each other through shared inflammatory pathways and metabolic disturbances. This scoping review aims to comprehensively explore the current body of literature on the interconnection between metabolic disorders and periodontal disease. A comprehensive literature search was conducted across databases, such as PubMed and Scopus. This review included studies that focusing on the relationship between metabolic disorders and periodontal disease, as well as articles written in English and published between 2019 and 2024. Non-peer-reviewed articles, articles that were not available in full text, and animal studies were excluded. A total 186 studies met the inclusion and exclusion criteria and were included in the review. Only 2.2% of the studies employed an experimental design, while a substantial majority (77.4%) utilized observational methodologies The majority of the research (72.0%) focused on adults, with a relatively small proportion (16.1%) dedicated to children and adolescents. Research focusing on specific populations, such as women with obesity or gestational diabetes, was limited (7.5%). This review identified a significant gap in intervention studies specifically targeting metabolic disorders to improve periodontal outcomes. Furthermore, it underscores the need for more focused research on vulnerable populations such as children, adolescents, and pregnant women.